2023
DOI: 10.1038/s41598-023-32782-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of adding poly-histidine tag on stability, antimicrobial activity and safety of recombinant buforin I expressed in periplasmic space of Escherichia coli

Abstract: The lack of cost-effective methods for producing antimicrobial peptides has made it impossible to use their high potential as a new and powerful class of antimicrobial agents. In recent years, extensive research has been conducted to decrease the cost of recombinant proteins production through microorganisms, transgenic animals, and plants. Well-known genetic and physiological characteristics, short-term proliferation, and ease of manipulation make E. coli expression system a valuable host for recombinant prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
9

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 41 publications
(66 reference statements)
0
2
0
9
Order By: Relevance
“…GRAVY score of our peptide is – 2.50. Peptides with a more negative GRAVY score are considered to be hydrophilic in nature hence good solubility and better bioavailability (Roshanak et al 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…GRAVY score of our peptide is – 2.50. Peptides with a more negative GRAVY score are considered to be hydrophilic in nature hence good solubility and better bioavailability (Roshanak et al 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…We confirmed that the commercial recombinant lysostaphin was not detected by the anti-His-tag antibody in Western blotting. To date, most chimeric lysins have been expressed with a His-tag, and the His-tag is known to be neutral to the antibacterial activity [24,46]. On the contrary, the added His-tag for the detection of chimeric lysins may decrease the antibacterial activity.…”
Section: Figure 5 the Determination Of The Minimal Inhibitory Volume ...mentioning
confidence: 99%
“…Ek olarak, E. coli hücreleri, rekombinant AMP ekstraksiyonu ve saflaştırma sürecini engelleyen çözünmeyen protein agregatları tarafından oluşturulan inklüzyon cisimcikleri üretebilir (Pouresmaeil vd., 2023). Tasarlanmış E. coli sitoplazmada veya periplazma rekombinant peptidi ihraç ederek peri-plazmik disülfid bağı izomerazını (DsbC) eksprese etmesine rağmen (Karyolaimos vd., 2021), bu bakteri diğer karmaşık translasyon sonrası modifikasyonları gerçekleştirmez (Roshanak vd., 2023). Bu nedenle, post-translasyonel modifikasyonlara ihtiyaç duyulan durumlarda, bu amaç için tasarlanmış mayalar veya bakteri suşları gibi başka sistemler seçilmelidir.…”
Section: Mi̇krobi̇yal Hücrelerde Rekombi̇nant Amp üReti̇mi̇unclassified
“…Genel olarak, birkaç mikroorganizmaya karşı aktivite gösterirler ve bazı durumlarda, bir immünomodülatör veya antitümör olarak hareket etme dahil olmak üzere birden fazla işlevi yerine getirebilirler, bu nedenle rastgele moleküller olarak kabul edilirler (Kiki, 2023). Yeni AMP bazlı ilaçların geliştirilmesi, biyoteknolojik çalışmalar ve farmasötik değerlendirme için bu moleküllerin büyük miktarlarda elde edilmesini gerektirir (Roshanak vd., 2023). Son birkaç yılda, birkaç yeni teknoloji nedeniyle AMP'lerin endüstriyel ölçekte üretilmesinde dikkate değer gelişmeler olmuştur (Chaudhary vd., 2023).…”
Section: Introductionunclassified
See 1 more Smart Citation